Muscarinic modulation of M and h currents in gerbil spherical bushy cells. - Charlène Gillet; Stefanie Kurth; Thomas Kuenzel (PLoS ONE)
Descending cholinergic fibers innervate the cochlear nucleus. Spherical bushy cells, principal neurons of the anterior part of the ventral cochlear nucleus, are depolarized by cholinergic agonists on two different time scales. A fast and transient response is mediated by alpha-7 homomeric nicotinic receptors while a slow and long-lasting response is mediated by muscarinic receptors. Spherical bushy cells were shown to express M3 receptors, but the receptor subtypes involved in the slow muscarinic response were not physiologically identified yet. Whole-cell patch clamp recordings combined with pharmacology and immunohistochemistry were performed to identify the muscarinic receptor subtypes and the effector currents involved. Spherical bushy cells also expressed both M1 and M2 receptors. The M1 signal was stronger and mainly somatic while the M2 signal was localized in the neuropil and on the soma of bushy cells. Physiologically, the M-current was observed for the gerbil spherical bushy cells and was inhibited by oxotremorine-M application. Surprisingly, long application of carbachol showed only a transient depolarization. Even though no muscarinic depolarization could be detected, the input resistance increased suggesting a decrease in the cell conductance that matched with the closure of M-channels. The hyperpolarization-activated currents were also affected by muscarinic activation and counteracted the effect of the inactivation of M-current on the membrane potential. We hypothesize that this double muscarinic action might allow adaptation of effects during long durations of cholinergic activation.